Integrated transcriptome and metabolome analysis of salinity tolerance in response to foliar application of choline chloride in rice (Oryza sativa L.) - Huo, Jingxin; Yu, Minglong; Feng, Naijie; Zheng, Dianfeng; Zhang, Rui; Xue, Yingbin; Khan, Aaqil; Zhou, Hang; Mei, Wanqi; Du, Xiaole; Shen, Xuefeng; Zhao, Liming; et al. (Frontiers in Plant Science, 2024)
Salt stress is one of the influential abiotic stresses as it sustains across the life cycle of plants. Choline Chloride (CC) effectively enhance salt tolerance in various crops, but molecular mechanisms of CCmediated salt tolerance in rice plant remains largely untapped. We carried out the morph-physiological, metabolomic and transcriptomic analysis to determine the regulatory mechanism of CC foliar application to rice seedlings under salt stress. Two rice varieties, "WSY (salt-tolerant)" and "HHZ (salt-sensitive)" seedlings were treated with 500 mg• L -1 CC under 0.3% NaCl stress. Our data revealed that foliar application of CC enhanced the morph-physiological parameters such as root traits, seedlings height, seedling strength index, seedling fullness, leaf area, photosynthetic parameters, photosynthetic pigments, starch and fructose content under salt stress in both rice varieties. Similarly, under salt stress, the CC treatment increased the activity of acid invertase, neutral invertase, sucrose synthase and amylase, and decreased the soluble sugar, sucrose and sucrose phosphate synthase. Comparative transcriptomic analysis showed that CC regulation combined with salt treatment induced changes in the expression of genes related to starch and sucrose metabolism, the citric acid cycle, carbon sequestration in photosynthetic organs, carbon metabolism, and photosynthetic antenna proteins in both rice varieties. KEGG pathway and enrichment analysis further confirmed these changes. Transcriptomic and metabolomic analysis showed that photosynthesis, carbon metabolism, and carbon fixation related pathways were crucial in CC-mediated salt tolerance. CC treatment enhances rice salt tolerance by activating distinct transcriptional cascades and phytohormone signaling jointly with multiple antioxidants and unique metabolic pathways. These results could provide a basis for revealing the mechanisms of metabolite synthesis and gene regulation induced by CC in rice in response to salt stress.The exogenous choline chloride treatment can significantly induce gene expression, physiological changes, and metabolism related to photosynthesis, thereby alleviating the impact of salt stress in rice.